2022
DOI: 10.1186/s12885-022-10186-2
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific lncRNA FAM99A may be a tumor suppressor and promising prognostic biomarker in hepatocellular carcinoma

Abstract: Background Increasing evidence shows that liver-specific long non-coding RNAs (lncRNAs) play important roles in the development of hepatocellular carcinoma (HCC). We identified a novel liver-specific lncRNA, FAM99A, and examined its clinical significance and biological functions in HCC. Methods The expression level and clinical value of FAM99A in HCC were examined using The Cancer Genome Atlas (TCGA), International Cancer Genome Consortium (ICGC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…This maintains CSC self-renewal capabilities along with high tumorigenic activities [ 225 ]. In liver cancer, lncRNA FAM99A was seen to act as a tumor suppressor, and its upregulation was seen to reduce colony formation, proliferation, and invasion of HCC cells making it a possible prognostic marker in HCC [ 226 ]. As lncRNA HDAC2 expression profiles are directly proportional to the severity of HCC, it may also act as a diagnostic marker during initial stages and a promising drug target during increased expression levels.…”
Section: Lncrnas As Markers and Therapeutic Targetsmentioning
confidence: 99%
“…This maintains CSC self-renewal capabilities along with high tumorigenic activities [ 225 ]. In liver cancer, lncRNA FAM99A was seen to act as a tumor suppressor, and its upregulation was seen to reduce colony formation, proliferation, and invasion of HCC cells making it a possible prognostic marker in HCC [ 226 ]. As lncRNA HDAC2 expression profiles are directly proportional to the severity of HCC, it may also act as a diagnostic marker during initial stages and a promising drug target during increased expression levels.…”
Section: Lncrnas As Markers and Therapeutic Targetsmentioning
confidence: 99%
“…lncRNAs have been in the clinical use as prognostic biomarkers of many complex diseases, including cancers (Tang et al, 2022;Huo et al, 2021). For example, liver-specific lncRNA FAM99A plays a cancerinhibiting role in hepatocellular carcinoma and might serve as its prognostic biomarker (Mo et al, 2022). Exosomal RP5-977B1 might be a diagnostic biomarker of non-small-cell lung cancer (NSCLC) (Min et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The family with sequence similarity 99 member A (FAM99A) gene was identified. Very recently, Mo et al reported the suppressor and prognostic effects of FAM99A on hepatocellular carcinoma (HCC) [8]. However, the deeper molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%